2019
DOI: 10.1016/j.asjsur.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for the accurate preoperative evaluation of the number of metastatic axillary lymph nodes in breast cancer

Abstract: Although we can pick up LNs that are likely to have metastasis on CT/US, it was impossible to accurately predict the number of metastases on CT/US. However, bedside-FNAC of suspicious LNs could accurately predict the number of metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
2
3
1
Order By: Relevance
“…In our study, the optimal cut-off value of cortical thickness was 3.3 mm. This is different from the results of Chen and Imai et al whose results are 3 mm [ 22 , 31 ].…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…In our study, the optimal cut-off value of cortical thickness was 3.3 mm. This is different from the results of Chen and Imai et al whose results are 3 mm [ 22 , 31 ].…”
Section: Discussioncontrasting
confidence: 96%
“…In terms of diagnosing lymph node status, this study demonstrated that LN metastasis of breast cancer is usually orderly, and SLN usually located at level I, which support the results of Kalli et al, namely, breast cancer cells spread progressively and orderly along the lymphatic drainage system, with level I first metastasis in most cases [ 30 ]. Both long-axis diameter and short-axis diameter of the metastasis SLN are significantly longer than that of the non-metastasis SLN, which is consistent with previous research results [ 31 , 32 ]. As for the short-axis diameter, it is recommended to distinguish between benign and malignant LNs in the RECIST 1.1 [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This proposed cutoff value was supported by but lower than that of March's finding in CT scan, which accepted 10 mm of short-axis for diagnosing lymph node metastasis in breast cancer (32). A recent study by Imai, N. and colleagues showed that, by CT scan, patients with ≥3 nodes meeting the criterion of both having a long-axis diameter ≥10 mm and a short-axis diameter ≥5 mm could be diagnosed with ALN metastasis (35). In our study, the average long-axis diameter in metastatic ALN was longer than that in non-metastatic counterparts by MDCT scan, however, no statistically significant difference was found between these two sets of ALN.…”
Section: Discussionmentioning
confidence: 99%
“…After AUS and US-FNAC, core needle biopsy (CNB) is recommended as the preoperative assessment. In daily practice, various methods are introduced for cytological preparation, such as conventional smear (CS), liquid-based preparation (LBP) and cell block [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , <...>…”
Section: Introductionmentioning
confidence: 99%